Examining the impact of time frame and perceived stress on the intention-planning-behavior link for physical activity among undergraduate students - Xu, Yue (Nanyang Technological University, 2024)
This thesis examines the role of time frame and perceived stress in the relationship between intention, planning, and physical activity (PA) behaviors among undergraduate students. Using the Health Action Process Approach (HAPA) as a theoretical framework, the thesis examined the interactions between HAPA factors, time frame, perceived stress, and PA. Three studies were conducted to observe the intention-planning-behavior link within different time frames (1 week, 2 weeks, and daily) with moderate to vigorous exercise (MVPA) as the outcome variable. Findings indicated that intention, action planning, and coping planning had a significant effect on physical activity, with the mediating effect of planning varying between different time frames. Perceived stress had no significant moderating effect on the intention-planning-behavior link. These results suggest that interventions to promote physical activity can potentially help address physical inactivity among young adults by adapting planning strategies to specific time frames.